(untitled) (Journal of Contemporary Issues in Accounting, 2023)
This paper examines the impact of IFRS adoption on earnings management of manufacturing firms in Nigeria. In this study IFRS does not have any proxies because the study is a comparative analysis that assesses earnings management pre- and post-IFRS adoption in the manufacturing sector of Nigeria, however, a dummy variable was developed to distinguish pre and post IFRS periods in the data analysis as shown below: Post-adoption = 1,Pre-adoption = 0. The study covers four years (2008-2011) Pre and four years (2016-2020) post-IFRS. This study modified the Jones (1991) model to measure earnings management in the manufacturing sector. The Logistic Regression was used in the analysis with aid of Statistical Package for Social Sciences (SPSS) version 20. Our findings revealed that earnings management measured by Discretionary Accrual was reduced after the adoption of IFRS and was statistically significant at 5% level. Based on the findings, the paper recommended that the mandatory adoption of IFRS should be embraced by all sectors of the Nigerian economy, all relevant factors such as CBN, accounting professional bodies, accounting academia, not only IFRS, should be considered in monitoring and creating an international competitive environment to ensure improvement in transparency and comparability of financial statements.